The Effectiveness of the Constant Time Delay Procedure in Teaching Reading and Writing with the Sound-Based Sentence Method - Emine Eratay; Ayten Düzkantar; Adnan Arı (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: The present study was planned since no practical study adapted for individuals with special needs (ISN) was found in teaching reading and writing with the sound-based sentence method (SBSM). There were few studies aimed at teaching reading and writing, and the skills targeted in these studies were limited. This study aimed to determine the effectiveness of the constant time delay procedure (CTDP) in teaching reading and writing with the sound-based sentence method to individuals with special needs. In addition to the said main purpose, the permanence of reading and writing skills and their generalizability across materials and persons were also examined. Moreover, the opinions of families and teachers of ISN were obtained to collect social validity data.Method: Three INS were included in this study. Of these, two were girls, and one was a boy, all aged seven. They attended the second grade as full-day co-teaching inclusive students and had not learned reading and writing. The study employed a multiple probe design across behaviors, one of the single-subject research designs. The study aimed to teach three behaviors and eighteen sub-behaviors, including six sub-behaviors in each behavior.Findings: The study showed that two participants acquired reading and writing skills in all the sub-behaviors (closed syllables, open syllables, three-letter monosyllables, three-letter two syllables, words, and sentences) of all three behaviors (syllables, words, and sentences consisting of e-l-a-k-i-n sounds, syllables, words, and sentences consisting of o-m-u-t-ü-y sounds, syllables, words, and sentences consisting of the combination of sounds in these two groups [e-l-a-k-i-n-o-m-u-t-ü-y]); that the skills they acquired were permanent; that they generalized these skills across persons and materials, while one participant acquired skills in the first three sub-behaviors (closed syllables, open syllables, three-letter monosyllables) only in the first behavior. Considering the social validity findings of the study, the participants’ families and primary school teachers expressed positive opinions about the study.Discussion: The findings obtained were discussed within the framework of the literature indicating the negative aspects of teaching reading and writing with the SBSM.